Theft by any other name is still theft: examining "looting" during the COVID-19 pandemic - Barranco, Raymond E. (Deviant behavior, 2023)
The current study examines newspaper reports of looting to answer two questions: (1) how was looting framed by U.S. newspapers during the COVID-19 pandemic and (2) did any looting actually occur? Looting after natural disasters, particularly hurricanes, has recently received increased attention in scholarly research. The crisis caused by the pandemic of SARS-CoV2 (hereafter COVID-19), while not a natural disaster, has provided many of the same opportunities for looting that have been previously observed following natural disasters. Our findings suggest looting charges were widely used, particularly in California, but that little actual looting took place. In fact, most of those situations referred to as "looting" were traditional property crimes that were treated as looting to enhance the penalty for the action. We conclude by discussing the implications of our findings for researchers and policymakers.